Minimally Invasive versus Conventional LVAD-Implantation—An Analysis of the Literature - Wachter, Kristina; Franke, Ulrich F.W.; Rustenbach, Christian J.; Baumbach, Hardy (The Thoracic and Cardiovascular Surgeon, 2019)
This review aims to provide an overview on recent data to evaluate minimally invasive (MVAD) and conventional (CVAD) left ventricular assist device (LVAD) implantation. A comprehensive literature search of PubMed, Cochrane Library, and ClinicalTrials.gov was conducted up to April 2017. A total of 183 studies were identified; 13 studies met inclusion criteria. The review revealed a trend toward a lower rate of transfusion, and shorter time for cardiopulmonary bypass, as well as a lower 30-day mortality rate for MVAD. This review indicates that there are possible benefits of minimally invasive LVAD implantation, even though the state of literature is poor.
Keywords: circulatory assist devices; heart failure; minimally invasive surgery; mini thoracotomy